Developing an Integrative Fintech Model for Productive Waqf Management: A Case Study of LMI Surabaya - Agung Wijayanto; Basar Dikuraisyin (Universitas Darul Ulum, 2026)
This study addresses the challenges of idle waqf assets and the continued reliance on conventional waqf management practices, which limit transparency, efficiency and public participation. To address these issues, the Infak and Sedekah Management Institution (LMI) Surabaya has undertaken a digital transformation through Sharia-compliant financial technology (fintech). This study aims to examine the transformation process and develop an Integrative Sharia Fintech Model for productive waqf management. Using a qualitative case study approach, data were collected through in-depth interviews, institutional documents, and digital platform observations, and analyzed through data reduction, display, interpretation, and conclusion drawing. The findings show that productive waqf management has been digitally transformed through the integration of platforms such as wakafo.org and lmizakat.org for fundraising, recording, management, monitoring, and reporting activities. This transformation improves operational efficiency, expands waqif participation, and enhances transparency and accountability. The study contributes by developing an Integrative Sharia Fintech Model consisting of three interconnected dimensions: Digital Technology Infrastructure, Waqf Governance and Institutional Management, and Sharia and Regulatory Compliance. The interaction among these dimensions creates an integrated productive waqf ecosystem that strengthens trust, participation, efficiency, and sustainability. The model extends the literature on Islamic social finance by providing a comprehensive framework for digital productive waqf management.